CORRECTING CLASS II MALOCCLUSION IN GROWING PATIENTS USING TWIN-BLOCK FOLLOWED BY FIXED APPLIANCES: CASE REPORT - Ishlahil Akmalia; Vina Andriani; Endah Mardiati (FKG ULM, 2025)
Background: Correcting Class II malocclusion with mandibular retrusion is challenging for orthodontists due to its multiple etiologies, especially in growing patients. The two-phase treatment is often considered effective for managing skeletal class II malocclusions in growing patients. Early intervention with functional appliances, such as Twin block, can effectively redirect growth in the desired direction. Objectives: This case report aims to present a two-phase orthodontic treatment approach using a Twin Block appliance followed by fixed appliances in an 11-year-old male patient with skeletal Class II malocclusion. Case: An 11-year-old male patient was diagnosed with skeletal class II malocclusion with a convex facial profile, retrusive chin, significant overjet (12 mm) and protrusive maxillary incisor. Pre-treatment cephalometric analysis showed SNA: 81°; SNB: 74°; <I-NA: 40°; I-NA: 7mm. Skeletal maturation assessment indicated the patient was at the peak of pubertal growth. Managing cases: A two-phase treatment approach was planned. Phase I involved growth modification using a Twin block appliance. Phase II consisted of fixed orthodontic treatment using the MBT 0.022 bracket system. The treatment was carried out for approximately 27 months, resulting in achieving skeletal class I, class I molar and canine relationship, with overjet reduced to 4 mm. Post treatment cephalometric analysis showed SNA: 81°; SNB: 78°; <I-NA: 30°; I-NA: 5.5 mm. Conclusion: A two-phase treatment using Twin Block followed by fixed appliances proved effective in correcting skeletal class II malocclusion with retrognathic mandible in growing patient. The treatment achieved normal occlusion, marked improvement in facial profile and patient satisfied with the result. Keywords: growing patient, mandibular retrusion, skeletal class II, twin block.